Towards More Speculative Critical Geographies - Noterman, Elsa (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
As capitalocentric, fascist, genocidal and techno-managerial visions of future space proliferate and coalesce, what is the role of critical geography? How can critical geographers foster the creative imaginaries needed to organise for alternative futures? Contemplating the possible future directions of critical geography, here I consider the function of speculation – both in terms of the critical geographies of speculation and the possibilities of speculative critical geographies. In a brief reflection on recent work, I think about the ways that critical geography allows for intervention in and cultivation of speculative futures.